HUBUNGAN TINDAKAN PEMELIHARAAN KESEHATAN GIGI DENGAN STATUS KEBERSIHAN GIGI DAN MULUT PADA MURID KELAS VII MADRASAH TSANAWIYAH NEGERI 8 KABUPATEN ACEH BESAR - Herry Imran; Nia Kurnia Wati (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
Taking care of oral health is the main preventive measure against dental and oral disorders. Based on the results of the initial examination on 20 students, the status of dental and oral hygiene were in the good category of 2 students, in the medium category was 7 people and 11 students were poor. as many as 8 students. The aim of the study was to determine the relationship between dental health care measures and oral hygiene status in class VII students at Madrasah Tsanawiyah Negeri 8 Aceh Besar district. This research was analytic with a cross sectional design, conducted on July 16-18 2019 with a population of 55 students, the study sample used a total sampling technique of 55 students. The data was collected by distributing questionnaires and data analysis using the chi-square statistical test with a = 0.05. The results showed that most dental health care measures were categorized as good 33 students (60%) while the most dental and oral hygiene statuses were those that due to the worst score 24 people (44%), and bivariate analysis showed that there was a relationship between dental health care measures and the students' oral hygiene status (p = 0.009). It is recommended to all respondents whose dental and oral hygiene status is poor to take dental healthmaintenance measures, especially brushing their teeth in a good and correct time and way